2012
DOI: 10.3109/s10165-011-0475-y
|View full text |Cite
|
Sign up to set email alerts
|

Six-transmembrane epithelial antigen of prostate4 (STEAP4) is a tumor necrosis factor alpha-induced protein that regulates IL-6, IL-8, and cell proliferation in synovium from patients with rheumatoid arthritis

Abstract: Human six-transmembrane epithelial antigen of prostate4 (STEAP4), an ortholog of mouse tumor necrosis factor-α-induced adipose-related protein (TIARP), plays a role in tumor necrosis factor (TNF)-dependent arthritis models. However, its role in rheumatoid arthritis (RA) is still obscure. This study explored such a role for STEAP4. The expressions of STEAP4, TNFα, and IL-6 were compared in synovia of RA and osteoarthritis patients. STEAP4 induction was examined in TNFα-stimulated fibroblast-like synoviocytes (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…For example, the NADH dehydrogenase 1 alpha subcomplex subunit 5 is part of the mitochondrial respiratory complex and has a regulatory role on inflammation. In the same line, the metallo-reductase STEAP4 down-regulates the production of inflammatory mediators such as IL8 and IL6 in human [50]. Similarly, prostaglandin reductase 1 catalyses an initial step of inactivation of leukotrien-B4.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the NADH dehydrogenase 1 alpha subcomplex subunit 5 is part of the mitochondrial respiratory complex and has a regulatory role on inflammation. In the same line, the metallo-reductase STEAP4 down-regulates the production of inflammatory mediators such as IL8 and IL6 in human [50]. Similarly, prostaglandin reductase 1 catalyses an initial step of inactivation of leukotrien-B4.…”
Section: Discussionmentioning
confidence: 96%
“…STEAP4 overexpression reduced rates of atherosclerosis and plaque formation in diabetic mice (Wang et al 2014), while its deficiency promoted atherosclerosis (Freyhaus et al 2012). Similarly, STEAP4 overexpression reduced migration of neutrophil-like HL60 (Tanaka et al 2012a) and reduced IL-6 and IL-8 cytokine expression (Tanaka et al 2012b), whereas siRNA knockdown of STEAP4 increased cytokine signaling in patients with rheumatoid arthritis (Tanaka et al 2012b), again consistent with a role for Steap4 in a negative feedback loop. These protective effects have also been observed in adipocytes and hepatocytes as discussed above.…”
Section: Regulatory and Protective Influences Of Steap4mentioning
confidence: 88%
“…Several reports show that Steap4 mRNA increases in a dose-dependent manner with TNFα exposure, suggesting TNFα accelerates STEAP4 synthesis (Moldes et al 2001; Chen et al 2009; Tanaka et al 2012a, b). Similar to the effect of TNFα, IL-6 exposure also results in an increase in Steap4 mRNA (Fasshauer et al 2004) and STEAP4 protein levels in human adipocytes (Chen et al 2010).…”
Section: Regulatory Influences On Steap4 Expressionmentioning
confidence: 99%
“…A number of genome-wide association studies suggest that STEAP4 is involved with numerous disorders related to obesity and metabolism including insulin resistance [8,9], metabolic syndrome [10,11], and insulin secretion [12,13]. Beyond its known role as a metalloreductase [14], studies have shown that STEAP4 plays an anti-inflammatory or protective role from cellular damage in adipocytes [15,9], mesangial cells [16], hepatocytes [1719], and synoviocytes [20]. In studies of mice, the STEAP4-/- phenotype includes the spontaneous development of obesity, insulin resistance, and eventual hyperglycemia [21], as well as signs of atherosclerosis [22], also suggesting a protective role for the protein.…”
Section: Introductionmentioning
confidence: 99%